Do pictures influence memory and metamemory in Chinese vocabulary learning? Evidence from Russian and Colombian learners (2023)
Despite the increasing interest in learning non-alphabetical languages such as Chinese, research about its learning process for alphabet users is scarce. Research conducted on Latin alphabet users on learning languages written in Latin alphabet, or on Chinese language learning in Chinese native speakers, users is undoubtedly useful but it does not inform about the peculiarities of leaning Chinese language by other alphabet users. Additionally, several authors have highlighted the need to inform and extend the current second language acquisition theories on the particular challenges of learning a language that uses another script. In this research we aim to contribute filling this research gap and studied the learning process of Chinese vocabulary by users of scripts different from Chinese. In particular, we examined the role of pictures and translations as learning aids for Chinese language vocabulary learning in participants familiarized with either one or two alphabetical scripts (different from the Chinese logographic script). One hundred thirteen participants studied word-aid pairs in different conditions: Hanzi (Chinese in Chinese characters)-picture; Pinyin (Chinese in Latin alphabet)-picture; Hanzi-translation; Pinyin-translation. Participants evaluated the future recallability of the words and their meanings (i.e., judgements of learning) and completed two recognition tests. Words in Pinyin and words-translation pairs were judged to be easier to remember than Hanzi and word-pictures pairs. Participants remembered the meaning of words written in Hanzi better than in Pinyin, and word-translations pairs better than pictures, but they were more confident about word-picture pairs. These results suggest that pictures boost confidence in learning Chinese, but do not affect performance. These findings suggest that while pictures may boost confidence in learning Chinese, they may not necessarily lead to better performance. Our study provides valuable insights into the interaction of learning aids and writing system in (meta)memory during vocabulary acquisition.